Sufism and Millennial Generation Movements in Modern Nusantara - Elmansyah Elmansyah; Muhammed Sahrin bin Haji Masri; Saimi bin Bujang (Al-Albab, 2019)
This article aims to show how Sufism has survived and existed in the history of Nusantara Islamic civilization. This is interesting, especially for the millennial generation, as an example of dealing with the swift currents of change and the desire to build the Indonesian Islamic Civilization within Islam Nusantara context. The data of the work is based on a comparative research project with a historical approach. The work suggests four key findings. First, the emergence of Sufism in the 3rd century of Hijri was part of the response in changes in Islamic civilization. Second, to counter the unexpected changes in time, the Sufis returned to the spiritual teachings, so as to avoid negativity. Third, a strong mentality of Sufis made them travel around the world to create a new civilization. Fourth, tolerant attitudes and models of the Sufis are the mainstays in achieving their mission.